Deradicalisation Crime Of Terrorism Actors By Police (Case Study In Police Jurisdiction Of Semarang) - Bagus Gani Setiana; Sri Kusriyah Kusriyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The paper titled